Analisis nilai karakter cerita nonfiksi dalam buku siswa kelas iv tema 7 “indahnya keragaman di negeriku” - Puji Prissetya Utami; Retno Winarni; Anesa Surya (Universitas Sebelas Maret, 2022)
Abstract. This research is a research with a qualitative descriptive approach. This research was conducted through several stages, namely reduction, classification, presentation, and drawing conclusions. This study aims to describe the character values of non-fiction stories contained in the fourth grade student book with the theme